Pengaruh Motivasi terhadap Niat Penggunaan Batik Bekasi - Ghefira Ghaetsa, Alda; Kabbaro , Hurriyyatun; Irwanto, Reno (DAS Institute, 2024)
This research was conducted to determine the influence of motivation on the intention to use Bekasi batik. The method used was associative quantitative with resident respondents in Kaliabang Tengah Subdistrict, North Bekasi. The number of respondents was around 100 people. This research was conducted from July to September 2024. This research used quantitative methods and was measured using intention to use instruments and motivation instruments. The results show that (1) the level of motivation among residents in Kaliabang Tengah Subdistrict is very high, (2) people have quite high intentions to use, (3) there is a very significant influence of motivation on intentions to use Bekasi batik, (4) amounting to 48, 9% can explain the significant influence of motivation on the intention to use Bekasi batik. Then a conclusion can be drawn from the research results, namely that there is a need to strengthen socialization to the Bekasi community